Renal function and long-term mortality in patients with asymptomatic carotid atherosclerosis - Hoke, Matthias; Pernicka, Elisabeth; Niessner, Alexander; Goliasch, Georg; Amighi, Jasmin; Koppensteiner, Renate; Minar, Erich; Mlekusch, Wolfgang; Rumpold, Helmut; Wagner, Oswald; Schillinger, Martin (Thrombosis and Haemostasis, 2012)
Renal dysfunction is a risk factor for mortality in patients with atherosclerosis. Estimated glomerular filtration rate (eGFR), cystatin C (CysC) and beta-2-microglobulin (B2M) are measures of renal function. It remains unclear, which of these parameters is the strongest predictor of outcome in patients with atherosclerosis. All-cause and cardiovascular mortality were prospectively investigated in 1,065 consecutive patients with asymptomatic carotid atherosclerosis. During a median follow-up of 6.3 years 275 patients died (25.8%), including 182 (66.2%) from cardiovascular causes. Estimated GFR, CysC and B2M were all significantly and independently associated with mortality. Inclusion of the renal parameters CysC and B2M but not of eGFR into a model with established cardiovascular risk factors improved the C-statistics significantly (p=0.0035 and 0.036, respectively; p=0.182 for eGFR). The net reclassification improvement (NRI) was 32.4% (p<0.0001) for CysC, 29% (p<0.0001) for B2M, and 16.5% (p=0.019) for eGFR. The integrated discrimination improvement (IDI) was 0.014 (p=0.0009) for CysC and 0.011 (p=0.005) for B2M while it was not significant for eGFR. Results were consistent for various subgroups with different extent of atherosclerosis. In summary, CysC and B2M were found to be independent predictors for mortality and had superior predictive value compared to eGFR in patients with asymptomatic carotid atherosclerosis. The clinical importance of these findings has to be validated in larger studies with a community-based approach.
Keywords: Atherosclerosis; risk factors; cerebrovascular disease; clinical studies